Relationship between Dietary Acid Load and Bone Health in Post-menopausal Women: A Systematic Review - Leila Moghari; Armin Ebrahimzadeh; Zahra Shamekhi; Nasrin Sharifi (Shiraz University of Medical Sciences, 2024)
Background: There is a lack of summarized reports of the relationship between dietary acid load (DAL) and bone health in post-menopausal women. Therefore, we aimed to design a systematic review and summarize eligible studies evaluating this association.Methods: The present study was a systematic review. From the literature search on PubMed, Google Scholar, Scopus, and Medline until March 2020, six studies comprising 2 crosssectionals, 2 cohorts, and 2 randomized control trials were selected and included in this study.Results: Four studies revealed a significant correlation between DAL and osteoporosis in post-menopausal women. In two reviewed studies, a significant association was seen between DAL and BMD, but in this association was not obtained in n another study. In addition, out of two randomized clinical studies (RCTs), one showed positive changes in bone markers when PRAL was decreased; however, no change was obtained in another RCT.Conclusion: The present study showed that post-menopausal women, especially those with a fracture history, may have a greater susceptibility to osteoporosis because of the detrimental effect of dietary acidity. In addition, DAL rather than protein might be the main risk factor for bone loss in this population. It should be noted that insufficient calcium intake may exacerbate bone loss following a high protein-high acid ash diet in these women.